PENGARUH PLANT GROWTH PROMOTING RHIZOBACTERIA TERHADAP BIOLOGI DAN STATISTIK DEMOGRAFI Thrips parvispinus (THYSANOPTERA: THRIPIDAE) PADA CABAI - Rudi Tomson Hutasoit (UNIVERSITAS LABUHANBATU, 2014)
Plant Growth Promoting Rhizobacteria (PGPR) is a group of bacteria that have been used as a bio-fertilizer to promote the nutrient plants supply and strengthen against plant pests and diseases. The aim of this study is knowing PGPR effect on long bean toward biology and demographic statistic Thrips parvispinus. The study was conducted by observing the development of the Thrips parvispinusfrom eggs to adulton chili pepper leaves with PGPR application or non-PGPR (control). The collected data were used to obtain information about the biology of the pest such as the stadia of each instar, preoviposition period, life cycle, adult longevity and fecundity. The data were also used to construct life tables for demographic statistic analysis using of the Jackknife method. PGPR usage have impact on thebiology of T. parvispinus such aslife cycle, longevity and fecundity. Gross reproduction rate (GRR), net reproductive rate (Ro), and intrinsic rate of increase (r) T. parvispinus with PGPR aplications lower than controls. PGPR can inhibit a doubling time (DT) T. parvispinus becomes longer than controls. Keywords: demographic statistics, life cycle, T. parvispinus